Trust in the Police and Willingness to Report Crimes: Who Researched the Nexus, When and with What Result? - Füstös, Mónika (Magyar Rendészet, 2024)
For many years criminology has assumed that the more victims trust the police, the more they will be willing to report crimes. Yet, the relationship between trust in the police and victims’ willingness to report has rarely been considered empirically. In the last few years, however, the topic has been attracting more and more attention worldwide. This study reviews the articles published on this topic in English so far and examines them from the perspective of scientific metrics, including the numerical distribution of the correlation. Using the search function of Web of Science, a total of 41 articles were found published between 1975 and 2020 that studied the relationship between the two concepts. Analysing these, it has emerged that research interest in the subject has increased over the past five years, primarily in criminology, but also in the fields of law and social sciences. The results also show that most research comes from economically more developed regions, mainly Anglo-Saxon areas. The main finding of this article is that the research results are inconsistent. Although most research confirms the relationship between trust in the police and willingness to report crimes, there are many studies that contradict this. Furthermore, the controversial results do not seem to correlate with the level of economic development, nor with when the research was published. Therefore, the relationship between trust in the police and the willingness to report crimes should also be researched using qualitative methods in order to gain a deeper understanding of this complex topic, and questionnaires should be designed specifically for this purpose.